The Biological Clock in Gray Mouse Lemur: Adaptive, Evolutionary and Aging Considerations in an Emerging Non-human Primate Model - Hozer, Clara; Pifferi, Fabien; Aujard, Fabienne; Perret, Martine (Frontiers in Physiology, 2019)
Circadian rhythms, which measure time on a scale of 24 h, are genetically generated by the circadian clock, which plays a crucial role in the regulation of almost every physiological and metabolic process in most organisms. This review gathers all the available information about the circadian clock in a small Malagasy primate, the gray mouse lemur (Microcebus murinus), and reports 30 years of published and unpublished data from the historical colony at Brunoy (France). Although the mouse lemur has long been seen as a “primitive” species, its clock displays high phenotypic plasticity, allowing perfect adaptation of its biological rhythms to environmental challenges (seasonality, food availability). The alterations of the circadian clock in M. murinus during aging show many similarities with those in human aging. Comparisons are drawn with other mammalian species (more specifically, with rodents, other nonhuman primates and humans) to demonstrate that the gray mouse lemur is a good complementary and alternative model for studying the circadian clock and, more broadly, brain aging and pathologies.